Assessments of neurodevelopmental functional impairments in Norwegian forensic reports on severe violent defendants - Bjørgen, Tale Gjertine (The journal of forensic psychiatry & psychology, 2025)
Adaptive behaviour is closely related to intellectual and neurodevelopmental functions. Impairment in these areas is associated with difficulties in education, work, and daily living. The ability to adapt to rules and laws may sometimes be affected. Therefore, impairments in adaptive functions may be relevant in the evaluation of criminal responsibility and potential special criminal sanctions, necessitating a special focus on neurodevelopmental functions and adaptive behaviours in forensic examinations. 100 Norwegian forensic reports were reviewed. Standard assessments and clinical and anamnestic descriptions of symptoms related to intellectual and neurodevelopmental conditions were recorded. Sub-criteria of neurodevelopmental diagnoses described were divided into four categories: intellectual impairment, adaptive dysfunctions, autism spectrum disorders, and attention deficit/hyperactivity disorder. The characteristics of the four categories were further explored. The description of at least one conditional category was detected in 84% of the reports, while 65% described more than two categories, and 43% described more than three categories. Symptoms from all four categories were described in 22%. Intellectual impairment symptoms were present in 57% of the reports. In only 12% of the reports a diagnosis regarding neurodevelopmental difficulties was set. The use of standardized assessments to explore neurodevelopmental functional symptoms as well as a discussion on related difficulties were limited. There is a need for more research, increased awareness, and training related to such impairments for forensic experts.